Software process improvement and capability determination : 17th International Conference, SPICE 2017, Palma de Mallorca, Spain, October 4-5, 2017, Proceedings /: 17th International Conference, SPICE 2017, Palma de Mallorca, Spain, October 4-5, 2017, Proceedings. (2017) - Unknown
No abstract available